The hadith of Jabir bin Abdullah, may Allah be pleased with them both, "In the acceptance of supplication on Wednesday " - Al- Atfy, Ahmed Eid (Journal of Islamic Sciences, 2021)
In this research, I took up and study the methods of modern Jabir bin Abdullah, may God be pleased with them, in the response to the supplication on Wednesday between the two prayers, and his evidence, I have followed the inductive, critical and analytical approach by collecting the methods of hadith and studying them in an objective scientific study and judging him by all his ways of working with him, if in the virtues of deeds, and that he is weak, In his bond and his consciences, and his denial, for his violation of history, and his monopoly on the reasons for publishing it, The research concluded with the most important results, including: that the large number of methods is not a condition for strengthening the hadith, but may be evidence of the severity of its weakness, and that the ijtihad of the Companion is not an agreed upon argument unless the companions spread and no opponent was known. and God knows best.
Keywords: Hadith; Supplication on Wednesday; Criticism of the Prophet's hadith